Gambaran Tingkat Pengetahuan Kesiapsiagaan Masyarakat Menghadapi Bencana Tanah Longsor di Jatiyoso Karanganyar - Kevin Seand Kiki Griffit Jesita; Endah Sri Wahyuni (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
landslides are geological natural disasters that can cause casualties and property losses are very much. According to BNBP (2021), Central Java is the province that has been hit by the most natural disasters since 2016 – 2020, reaching 3,693 incidents. Karanganyar regency is one of the areas prone to landslides. Preparedness is one of the efforts made to anticipate possible disasters to avoid casualties, property losses and changes in the order of life in the community. To describe the level of knowledge of community preparedness for landslides in Jatiyoso. descriptive research method with quantitative approach. This researcher uses purposive sampling technique. obtained an overview of the level of knowledge of community preparedness for landslides at most is good as many as 79 respondents by 55.6%. The characteristics of respondents based on gender were 75 respondents by 52.8 %, based on age at most 26-35 years old, namely 111 respondents by 78.2%, based on education at most high school/high school, namely 78 respondents by 54.9%. The level of knowledge of community preparedness for landslides has a good category in Jatiyoso Karanganyar.